Interferometric meteor head echo observations using the Southern Argentina Agile Meteor Radar. Issue 3 (25th March 2014) - Janches, D.; Hocking, W.; Pifko, S.; Hormaechea, J. L.; Fritts, D. C.; Brunini, C.; Michell, R.; Samara, M.
<x xml:space="preserve">Abstract</x> A radar meteor echo is the radar scattering signature from the free electrons generated by the entry of extraterrestrial particles into the atmosphere. Three categories of scattering mechanisms exist: specular, nonspecular trails, and head echoes. Generally, there are two types of radars utilized to detect meteors. Traditional VHF all‐sky meteor radars primarily detect the specular trails, while high‐power, large‐aperture (HPLA) radars efficiently detect meteor head echoes and, in some cases, nonspecular trails. The fact that head echo measurements can be performed only with HPLA radars limits these studies in several ways. HPLA radars are sensitive instruments constraining the studies to the lower masses, and these observations cannot be performed continuously because they take place at national observatories with limited allocated observing time. These drawbacks can be addressed by developing head echo observing techniques with modified all‐sky meteor radars. Such systems would also permit simultaneous detection of all different scattering mechanisms using the same instrument, rather than requiring assorted different classes of radars, which can help clarify observed differences between the different methodologies. In this study, we demonstrate that such concurrent observations are now possible, enabled by the enhanced design of the Southern Argentina Agile Meteor Radar (SAAMER). The results presented here are derived from observations performed over a period of 12 days in August 2011 and include meteoroid dynamical parameter distributions, radiants, and estimated masses. Overall, the SAAMER's head echo detections appear to be produced by larger particles than those which have been studied thus far using this technique.